PENGARUH STRES KERJA DAN KUALITAS TERHADAP TURNOVER INTENTION PERAWAT DI MASA PANDEMI COVID-19 - Galih Nadhova Imana; Muhardi Muhardi (Universitas Prima Indonesia, 2022)
Coronavirus Disease 2019 (COVID-19) caused by infection with severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) has been declared a pandemic since March 2020. COVID-19 has had an impact on increasing the workload and risk on nurses, thus affecting the level of stress and quality of life of nurses. The purpose of this study was to determine the effect of work stress and quality of life on nurses' turnover intention. This study used an observational analytic design with a cross-sectional design with proportional stratified random sampling of the population of inpatient nurses. The number of samples was 215 respondents using the WHOQOL-Brief Questionnaire and a validated questionnaire. The results showed that the average score of work stress was 3.40 (enough), the average quality of life score was 2.59 (low), and the average score was 3.44 (high). Partial analysis of the work stress variable has a significant and positive impact on turnover intention, while the quality of life variable has a significant and negative impact on turnover intention. Meanwhile, the simultaneous analysis shows that the variables of work stress and quality of life have an impact on turnover intention. This is because during the COVID-19 pandemic there was an increase in workload, work risk and anxiety from nurses. In addition, nurses experience rest disturbances, and a decrease in social activities so that this encourages nurses to leave their jobs during this COVID-19 period.